2012
DOI: 10.1007/s00234-012-1115-8
|View full text |Cite
|
Sign up to set email alerts
|

Late clinical and radiological complications of stereotactical radiosurgery of arteriovenous malformations of the brain

Abstract: Major radiation injury is frequent and increases the risk of neurological complications. Its late appearance implies that current follow-up protocols need to be extended in time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 21 publications
0
32
0
1
Order By: Relevance
“…30% of patients treated with SRS for AVMs, follow-up neuroimaging studies demonstrated transient changes, namely a high-signal region on T2weighted spin-echo MRI or a low attenuation area on CT in areas surrounding the treatment volume that had previously appeared normal. 15,22,26,29,31 Levegrün et al 28 and Tu et al 49,50 attributed these image-defined responses following AVM SRS to either postradiation changes (i.e., blood-brain barrier injury or interstitial vasogenic edema or both) or to a local biological effect in the adjacent brain parenchyma (i.e., reactive astrogliosis) in response to AVM obliteration. Kondziolka et al 31 reported that the incidence of appearance of transient perilesional brain edema is more frequent after SRS for AVMs than after SRS for brain tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…30% of patients treated with SRS for AVMs, follow-up neuroimaging studies demonstrated transient changes, namely a high-signal region on T2weighted spin-echo MRI or a low attenuation area on CT in areas surrounding the treatment volume that had previously appeared normal. 15,22,26,29,31 Levegrün et al 28 and Tu et al 49,50 attributed these image-defined responses following AVM SRS to either postradiation changes (i.e., blood-brain barrier injury or interstitial vasogenic edema or both) or to a local biological effect in the adjacent brain parenchyma (i.e., reactive astrogliosis) in response to AVM obliteration. Kondziolka et al 31 reported that the incidence of appearance of transient perilesional brain edema is more frequent after SRS for AVMs than after SRS for brain tumors.…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25] In $ 30% of patients treated with SRS for AVMs, follow-up neuroimaging studies demonstrated transient changes, namely a high-signal region on T2-weighted spin-echo MRI in areas surrounding the target and that had previously appeared normal. 23,[26][27][28][29] These changes are usually observed 6 to 18 months after SRS and are frequently transient. 27,30 The purpose of the present work was to study the MRIdefined changes following photon SRS of AVMs and specifically to correlate the appearance of perinidal T2 hyperintensity signal with the eventual angiographic obliteration of the AVM nidus in response to SRS treatment.…”
Section: Introductionmentioning
confidence: 99%
“…We report no post-treatment hemorrhage, 4.5% (1/22) of patients developing perilesional edema, and no radiation necrosis at an average dose of 15.6Gy. Parkhtik et al 49 , in a study of 102 patients, noted perilesional edema in 43.1% of patients and had 6.9% of patients develop radiation necrosis with an average radiation dose of 18.5 Gy. Similarly the University of Pittsburgh group 50 has reported the development of perilesional imaging changes in approximately 30% of patients in numerous studies.…”
Section: Discussionmentioning
confidence: 99%
“…28 Late complications can include cyst formation, progressive vasogenic edema, and chronic expanding hematoma development. 16,25,26 Preliminary data from Lee and colleagues (Lee CC et al, unpublished data) have shown that the risks of adverse radiation effects are reduced if radiation exposure of intervening normal brain is minimized, especially in diffuse forms of AVMs. These authors have therefore developed, using fuzzy c-means clustering techniques, a method of separating CSF, brain tissue, and AVM vasculature on high-resolution T2-weighted images, producing color-coded maps of the AVM showing these 3 components separately in order to help guide GKSRS planning.…”
Section: Imaging Techniquesmentioning
confidence: 99%